Efforts to Improve Student Learning Outcomes in Natural Science Lessons Material Plant Body Parts Through Cooperative Type Team Games Tournament in MI Negeri 4 Asahan - Fadhliah (Indonesian Journal of Education and Social Humanities, 2024)
This research aims to improve the learning outcomes of students in the Natural Sciences subject, especially in the material "Parts of the Plant Body" through the application of a cooperative learning model of the Team Games Tournament type at Madrasah Ibtidaiyah Negeri 4 Asahan. The background of this research is based on the low learning outcomes of students which can be seen from the number of students who have not yet reached the Minimum Completion Criteria (KKM). The research method used is Classroom Action Research which is carried out in two cycles, and each cycle consists of stages of planning, implementation, observation, and reflection. The subjects of this research are 25 class IV students. Data collection techniques include tests of learning outcomes, observation of teacher and student activities, as well as documentation. The results of the research show that there is a significant increase in student learning outcomes from pre-cycle to cycle I, and from cycle I to cycle II. In the first cycle, the average grade of students increased but the completeness of learning was not yet maximal. After the improvement of learning in cycle II, the learning outcomes of students experienced a higher increase, and the completion of learning reached more than 88%. In addition, the TGT learning model also increases active participation, cooperation, and student learning motivation during the learning process. From the results of this research, it can be concluded that the application of the cooperative learning model of the Team Games Tournament type is effective in improving student learning outcomes in IPA subjects, especially plant body material. Therefore, this learning model can be used as an alternative learning strategy that is interesting and enjoyable for primary school students, especially in primary madrasahs.